Action Research for Curriculum Improvement in Pre-Registration Midwifery Education - Fraser, Diane M (1998)
This thesis examines the effectiveness of a new curriculum for the preparation of midwives. Data were collected over a three year period in seven case study institutions, from women who had their babies in one large maternity unit and from a professional network of experienced midwives whose role is to advise the statutory body regulating midwifery programmes in England.